Clinical Association Between Psychotic Symptoms and the Gilbert Syndrome: A Case Report - Balaswamy Reddy; Alessandra Nocera; Renato de Filippis; Soumitra Das (Neuropsychiatric Investigation)
Modern research in psychiatry is increasingly focusing on the possible identification of potentially useful biomarkers for early and differential diagnosis and patient-tailored therapy. In this context, old and new biomarkers are gaining attention, and bilirubin could represent a low-cost and widespread tool in this regard. In the following paper, we present a case report of a patient with juvenile-onset schizophrenia successfully treated with oral risperidone on 2 separate occasions, whose clinical exacerbation phases overlapped with hyperbilirubinemia peaks, while comfort phases were associated with serum bilirubin within the normal range. The patient was later diagnosed with Gilbert’s syndrome, a benign, congenital condition of hyperbilirubinemia, with alternating phases of mostly asymptomatic bilirubin levels. This case highlights a possible relationship between psychotic symptoms and plasma bilirubin levels. While not representing by itself a sufficient condition to determine a relationship between the 2 phenomena, it poses a relevant question for future clinical and research investigations.